2018
DOI: 10.21037/jtd.2018.03.67
|View full text |Cite
|
Sign up to set email alerts
|

Cold crystalloid versus warm blood cardioplegia in patients undergoing aortic valve replacement

Abstract: Background: Myocardial protection techniques during cardiac arrest have been extensively investigated in the clinical setting of coronary revascularization. Fewer studies have been carried out of patients affected by left ventricular hypertrophy, where the choice of type and temperature of cardioplegia remain controversial.We have retrospectively investigated myocardial injury and short-term outcome in patients undergoing aortic valve replacement plus or minus coronary artery bypass grafting with using cold cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…It appears that the use of autologous blood as cardioplegia is the most plausible option since it is more physiological and has high oxygen-carrying capacity and lower haemodilution, contrary to its crystalloid counterparts. However, no clear superiority has been demonstrated in any comparative studies with BC and crystalloid-based formulas 13 , 14 . A current meta-analysis has indicated that smaller volumes of cardioplegia should be used in patients receiving DNC 8 .…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the use of autologous blood as cardioplegia is the most plausible option since it is more physiological and has high oxygen-carrying capacity and lower haemodilution, contrary to its crystalloid counterparts. However, no clear superiority has been demonstrated in any comparative studies with BC and crystalloid-based formulas 13 , 14 . A current meta-analysis has indicated that smaller volumes of cardioplegia should be used in patients receiving DNC 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analysis was performed for all the outcomes using the leave-one-out method. Removal of individual studies from the analysis did not alter the statistical significance, except for the exclusion of Nardi and colleagues 9 in hospital LOS, which would result in statistically significant (P ¼ .04) shorter LOS in warm cardioplegia arm.…”
Section: Resultsmentioning
confidence: 97%
“…56,57 However, many results of animal studies have since shown that warm cardioplegia may be safely interrupted for about 10 min without det rimental effects. 10,58,59 In one animal study, no detrimen tal effects were seen after ischemic periods of up to 15 Better myocardial protection and less frequent use of IABP and lower peak CK-MB level in early postoperative period in warm group than in cold group Zeriouh M, et al 50 (2015) Evaluation of warm and cold cardioplegia in emergency vs elective settings Similar short-and long-term outcomes in cold and warm cardioplegia across elective and emergency settings Nardi P, et al 39 (2018) Investigation of myocardial injury and short-term outcome in patients undergoing cold crystalloid or warm blood cardioplegia Lower CK-MB, troponin I, and aspartate aminotransferase levels at time 0 in cold crystalloid group than in warm blood group; no significant difference in perioperative MI, postoperative major complications, or in-hospital mortality rates AVR = aortic valve replacement; CK-MB = creatine kinase-myocardial band enzyme; IABP = intra-aortic balloon pump; MI = myocardial infarction min. 60 These findings correlated with those in human studies.…”
Section: Duration Of Ischemic Intervalsmentioning
confidence: 99%
“…38 These results were mirrored by those of a recent study in which warm blood cardioplegia was found to be inferior to cold crystalloid cardioplegia in patients with severely hypertrophic LVs who underwent aortic valve surgery. 39 These differences in myocardial markers of ischemia, however, do not appear to translate into inferior clini cal outcomes. Calafiore and coauthors 40 retrospectively compared patients who underwent intermittent ante grade warm or intermittent antegrade cold cardioplegia for valve surgery and found significantly lower cardiac related mortality rates in the warm cardioplegia group (P <0.01).…”
Section: Outcomes Of Warm Versus Cold Cardioplegiamentioning
confidence: 99%